Propuesta de un Plan de Comunicación Organizacional para Fortalecer la Cultura e Identidad de la Empresa Incavit S.A - Viteri Mendieta, Jourdan Nicolette (2015)
INCAVIT S.A is a company that produces and sells construction material such as steel sheets, tools, zinc, and rubber. It is a family-owned business that has widens its range of offered products gradually in time. It is located in several cities in the Coastal Region of Ecuador and it employs a team of around 50 people. The parent company is located in Santo Domingo de los Tsáchilas, and the other branches are located in Quevedo, Guayaquil, Esmeraldas, and Portoviejo. This investigation is a part of the efforts made to maintain a constantly changing and improving company. Its purpose is to identify how the communication within the organization has been managed as well as to identify if the internal public feels satisfied in its place of work. Based on this, and in order to strengthen the culture and corporate identity, an Organizational Communication Plan is proposed. The first chapter addresses the theoretical frame about information regarding corporate communication as well as other information relevant to this project such as the basic concepts of organizational culture and identity. The second chapter addresses information about the company and the business environment in which it operates. Information regarding the research performed to identify the current status of the internal communication is found on the third chapter. Finally, the fourth and last chapter presents the communication plan proposed as well as the conclusions and recommendation.